SAE Technical Paper Series 2011
DOI: 10.4271/2011-01-1058
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Edge Fracture in Various Types of Advanced High Strength Steel

Abstract: In vehicle crash events there is the potential for fracture to occur at the processed edges of structural components. The ability to avoid these types of fractures is desired in order to minimize intrusion and optimize energy absorption. However, the prediction of edge cracking is complicated by the fact that conventional tensile testing can provide insufficient data in regards to the local fracture behavior of advanced high strength steels. Fracture prediction is also made difficult because there can be inade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…An optical online measurement system was used with a gauge length of 2 mm for the determination of the fracture strain as well as a punch force measurement [59]. The curve shape of the punch force displacement curve can be used to differentiate between the edge-crack sensitivities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An optical online measurement system was used with a gauge length of 2 mm for the determination of the fracture strain as well as a punch force measurement [59]. The curve shape of the punch force displacement curve can be used to differentiate between the edge-crack sensitivities.…”
Section: Discussionmentioning
confidence: 99%
“…A symmetrical specimen with a width of 50 mm and semicircle notch with a radius of 10 mm was proposed by [59]. Here edges made by water jet, laser and punching were compared.…”
Section: Cuttingmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that edge quality can affect fracture strain, and materials with punched edge exhibit failure initiation from edge, showing lower fracture strain than samples with higher quality edge preparation. 14) Figures 9(b) and 9(d) present the DIC images of the weld samples containing a HAZ just before failure initiation. Failure initiated in the HAZ and center of sample regardless of edge quality, and propagated through HAZ and base metal until full material separation was achieved.…”
Section: Fracture Strain Of Welded Samples Vs Base Materialsmentioning
confidence: 99%